Retraction Note to: Implications of Entropy and Surgical Pleth Index-guided general anaesthesia on clinical outcomes in critically ill polytrauma patients. A prospective observational non-randomized single centre study. - Rogobete, Alexandru Florin; Sandesc, Dorel; Cradigati, Carmen Alina; Sarandan, Mirela; Papurica, Marius; Popovici, Sonia Elena; Vernic, Corina; Bedreag, Ovidiu Horea (Journal of Clinical Monitoring & Computing, 2020)
The authors have retracted this article [1]. After publication it was discovered that Table 1 which reports the clinical and demographical characteristics of the patients in the study contains a number of statistical and typographical errors. The data reported in this article are therefore unreliable. All authors agree with this retraction.